Nutritional and multi-elemental profile of indigenous and underutilized Solanum species of Sikkim, India - Khatoon, Uzma; Sharma, Laxuman (Bangladesh Journal of Botany, 2019)
In the present study, three Solanum species (Solanum torvum, S. aethiopicum and S. macrocarpon) were evaluated using recommended methods for nutritional and multi-elemental composition. The nutritional and multi-elemental profile varied significantly among all three species. When compared with the nutritive value of close commercial relatives i.e., cultivated brinjal (Solanum melongena L.), these crops were found better in many aspects. The result highlights the nutritional importance of lesser known though very important vegetables and also points towards the need to promote increased consumption and conserve genetic resources.